2017
DOI: 10.5194/bg-2017-533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global change effects on decomposition processes in tidal wetlands: implications from a global survey using standardized litter

Abstract: Tidal wetlands, such as tidal marshes and mangroves, are hotspots for carbon sequestration. The preservation of organic matter (OM) is a critical process by which tidal wetlands exert influence over the global carbon cycle and at the same time gain elevation to keep pace with sea-level rise (SLR). The present study provides the first global-scale field-based experimental evidence of 50 temperature and relative sea level effects on the decomposition rate and stabilization of OM in tidal wetlands. The study was … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…While our study did not partition R eco between microbial and autotrophic respiration, the most parsimonious explanation for our results is that changes in R eco were due to changes in soil microbial activity, given the similar levels of above and belowground biomass in our study ( Figure 2). In addition, previous research at our site has demonstrated that fertilization with NO 3 -, which is a strong electron acceptor, has stimulated denitrification (Koop-Jakobsen and Giblin 2010), increased litter respiration (Deegan et al 2012), and decreased soil organic matter stabilization (Mueller et al 2017). Work in another temperate tidal salt marsh, the Great Sippewisset Marsh, has demonstrated that N enrichment can alter the active soil microbial community to favor denitrifying bacteria (Peng et al 2016) and increase R eco (Martin et al 2018).…”
Section: Discussionmentioning
confidence: 64%
“…While our study did not partition R eco between microbial and autotrophic respiration, the most parsimonious explanation for our results is that changes in R eco were due to changes in soil microbial activity, given the similar levels of above and belowground biomass in our study ( Figure 2). In addition, previous research at our site has demonstrated that fertilization with NO 3 -, which is a strong electron acceptor, has stimulated denitrification (Koop-Jakobsen and Giblin 2010), increased litter respiration (Deegan et al 2012), and decreased soil organic matter stabilization (Mueller et al 2017). Work in another temperate tidal salt marsh, the Great Sippewisset Marsh, has demonstrated that N enrichment can alter the active soil microbial community to favor denitrifying bacteria (Peng et al 2016) and increase R eco (Martin et al 2018).…”
Section: Discussionmentioning
confidence: 64%
“…Tremendous efforts at mitigating N loading to coastal waters have improved conditions in some regions (Zedler 2000, Warren et al 2002, however, worldwide, many salt marshes continue to experience chronic nutrient enrichment (Bricker et al 2008. The implications of this nutrient enrichment for C storage in salt marshes remain unclear, with some studies documenting an increase in primary production (Valiela et al 1975, Morris et al 1991, Morris et al 2013, and others indicating decreased belowground biomass (Langley et al 2009, Watson et al 2014, increased respiration of OM (Wigand et al 2009, Watson et al 2014, and decreased sediment stability , Mueller et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although nitrate is typically limiting in coastal waters (Ryther & Dunstan 1979), nutrient enrichment from fertilizer production, agricultural and urban runoff, enriched groundwater, and atmospheric deposition may increase its availability to sediment microbes . Increased supplies of nitrate can stimulate respiration of belowground OM by providing additional reducing capacity to the system (Bulseco-McKim et al In review), which can lead to lower sediment stability and potential marsh collapse , Mueller et al 2018.…”
Section: Introductionmentioning
confidence: 99%